2018
DOI: 10.1007/s00401-018-1897-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of amyloid distribution by [18F]flutemetamol PET predicts the neuropathological phase of amyloid β-protein deposition

Abstract: The deposition of the amyloid β-protein (Aβ) in senile plaques is one of the histopathological hallmarks of Alzheimer’s disease (AD). Aβ-plaques arise first in neocortical areas and, then, expand into further brain regions in a process described by 5 phases. Since it is possible to identify amyloid pathology with radioactive-labeled tracers by positron emission tomography (PET) the question arises whether it is possible to distinguish the neuropathological Aβ-phases with amyloid PET imaging. To address this qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(80 citation statements)
references
References 40 publications
6
72
2
Order By: Relevance
“…However, there is still a great deal of variability present in the amyloid positivity thresholds derived from this approach (Su et al, 2018). A further limitation of amyloid PET imaging modalities is that there is a lack of concordance with Aβ plaque phases as determined by pathohistological methodology, such as Thal stages PET was unable to accurate predict the target Aβ stages in 27.84% of cases in an end-of-life cohort (Thal et al, 2018). Additionally, an amyloid positivity threshold of a standardised uptake value ratio of 1.5…”
Section: F-labelled Amyloid Tracersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is still a great deal of variability present in the amyloid positivity thresholds derived from this approach (Su et al, 2018). A further limitation of amyloid PET imaging modalities is that there is a lack of concordance with Aβ plaque phases as determined by pathohistological methodology, such as Thal stages PET was unable to accurate predict the target Aβ stages in 27.84% of cases in an end-of-life cohort (Thal et al, 2018). Additionally, an amyloid positivity threshold of a standardised uptake value ratio of 1.5…”
Section: F-labelled Amyloid Tracersmentioning
confidence: 99%
“…A strong discriminative ability of [ 18 F]florbetapir for AD and MCI compared to a cognitively normal status is supported by a number of additional studies (Degenhardt et al, 2016;Johnson et al, 2013;Namiki et al, 2015). However, there is still a great deal of variability present in the amyloid positivity thresholds derived from this approach (Su et al, 2018 PET was unable to accurate predict the target Aβ stages in 27.84% of cases in an end-of-life cohort (Thal et al, 2018). This is due to a range of factors including variability in scanning time, methodology employed during analyses, identified reference regions and regions of interest, attenuation correction, partial volume correction, machines used to scan, and tracer-specific properties.…”
Section: Introductionmentioning
confidence: 97%
“…Multiple studies of AD, MCI, and aged non-demented controls demonstrated high correspondence between postmortem amyloid pathology and antemortem amyloid PET imaging using [C-11]PiB (Bacskai et al, 2007;Burack et al, 2010;Ikonomovic et al, 2008;Kadir et al, 2011;Kantarci et al, 2012;Sojkova et al, 2011) and related F-18 labeled ligands Florbetapir (Clark et al, 2012) and Flutemetamol (Curtis et al, 2015;Ikonomovic et al, 2016Ikonomovic et al, , 2018Thal et al, 2018). In contrast, little work has been done to elucidate neuropathology substrates of amyloid PET ligands in DS cases.…”
Section: Imaging-to-autopsy Studies Of Amyloid Pet Ligands In Dsmentioning
confidence: 99%
“…Amyloid imaging with positron emission tomography (PET) has become an important diagnostic tool for AD (Villemagne et al, 2011), displaying high sensitivity and specificity by comparison with neuropathological findings (Clark et al, 2012;Sabri, Seibyl, Rowe, & Barthel, 2015;Villeneuve et al, 2015). Recent amyloid PET studies have attempted to characterize and stage the regional amyloid pathology spread in-vivo, either using an a priori distinction between early neocortical and later subcortical amyloid deposition (Cho et al, 2018;Hanseeuw et al, 2018;Thal et al, 2018) or more comprehensive data-driven models including regional deposition differences within both cortical and subcortical areas (Cho et al, 2016;Grothe et al, 2017;Sakr et al, 2019). In our previous work (Grothe et al, 2017) we have developed an in-vivo staging model that adopts a commonly used analytic approach for determining regional staging schemes in neuropathological studies (Braak & Braak, 1991;Josephs et al, 2016;Thal et al, 2002) and is based on the frequency of regionally measured uptake positivity in cognitively normal older participants.…”
mentioning
confidence: 99%